2004
DOI: 10.4319/lo.2004.49.5.1840
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in the abundance of Jesogammarus annandalei (Tattersall) in Lake Biwa

Abstract: Changes in the abundance of an endemic amphipod, Jesogammarus annandalei, that inhabits the profundal zone of Lake Biwa were examined from 1966 to 1999. The abundance of J. annandalei increased suddenly during the mid1980s and thereafter stayed at a level that was sevenfold higher than that before 1980. Compared with the amphipod in the 1960s, both the clutch and body size of the matured individuals decreased during the 1990s, which suggests that per capita food supply decreased. Thus, the increase in the abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…This value means that $4.5 g O 2 m À3 was consumed in the deep layer with 25 m of thickness if RQ=1. In agreement with this estimate, $4-6 g O 2 m À3 has been consumed every year during the thermally stratified period at deep depths in Lake Biwa since 1970 (i.e., Ishikawa et al 2004). Thus, although the carbon mineralization rate is much lower in the deep layer compared with the surface layer, further increases in the rate would result in serious impacts on the chemical environments at deep depths in Lake Biwa (see also Murase et al 2005).…”
Section: Discussionsupporting
confidence: 59%
“…This value means that $4.5 g O 2 m À3 was consumed in the deep layer with 25 m of thickness if RQ=1. In agreement with this estimate, $4-6 g O 2 m À3 has been consumed every year during the thermally stratified period at deep depths in Lake Biwa since 1970 (i.e., Ishikawa et al 2004). Thus, although the carbon mineralization rate is much lower in the deep layer compared with the surface layer, further increases in the rate would result in serious impacts on the chemical environments at deep depths in Lake Biwa (see also Murase et al 2005).…”
Section: Discussionsupporting
confidence: 59%
“…At the same time, gammarids ( Jesogammarus annandalei ), another common prey of G. isaza [25], suddenly increased in population density through release from top-down regulation by G. isaza (Fig. 1d; also see [32]). …”
Section: Introductionmentioning
confidence: 98%
“…Intriguingly, G. isaza has adapted to a pelagic habitat with its strong swimming ability, whereas most gobiid fish are benthic. As a result of this strong swimming ability, this species plays important roles in the lake ecosystem as a keystone predator by feeding on pelagic zooplankton and benthic gammarid amphipods [25], [32], thereby coupling the pelagic and benthic food webs of the lake. Through stomach content analysis, Nakanishi and Nagoshi [25] reported that G. isaza fed mainly on zooplankton and gammarids in the 1960s.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, Tsai et al (2016) reanalyzed long-term dietary data for an omnivorous predatory fish species collected from a lake ecosystem over four decades (Briones et al 2012) by incorporating environmental abundance data for its major prey, zooplankton and zoobenthos (Ishikawa et al 2004;Hsieh et al 2011). Specifically, they compared prey size compositions in predator guts and the environment (i.e., the realized versus the environmental PPMR) to detect deviations between these elements as effects of the preferred PPMR.…”
Section: Realized Versus Preferred Predator-prey Mass Ratiomentioning
confidence: 99%